PILKADES DAN PERANG SIMBOLIK:KRITIK SOSIAL DAN GENDER DALAM MASYARAKAT ADAT (KAJIAN ATAS CERPEN “PILKADES” KARYA SILVESTER PETARA HURIT) - Vinsensius Crispinus Lemba; Theresia Jawa Da Silva (Prakata: Jurnal Bahasa dan Sastra Indonesia Serta Pembelajaran, 2025)
This study aims to describe Pilkased and symbolic war: social criticism in indigenous communities (A study of the short story "Pilkades" by Silvester Petara Hurit. This study uses the approaches of social criticism, feminist criticism, and literary psychology. The findings and discussion of the short story "Pilkades" and Symbolic War: Social and Gender Criticism in Indigenous Communities" by Silvester Petara Hurit show that there is social and gender criticism in indigenous communities which is concluded as follows, (1) Custom and Hegemony of Power in Social Criticism, (2) Deconstruction of Democracy: Inequality in Local Politics, (3) Gender, Representation of Women, and Feminist Criticism, and (4) Mysticism, Symbolic War, and Cultural Criticism.